2021
DOI: 10.3390/polym13162793
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dental Glass Fibers and Orthopedic Mesh on the Failure Loads of Polymethyl Methacrylate Denture Base Resin

Abstract: The aim of the present study was to evaluate the fracture loads of polymethyl methacrylate (PMMA) complete denture bases reinforced with glass-fiber mesh and orthopedic casting tape (OCT) in comparison to conventional PMMA dentures under artificial aging. Dental fiberglass framework (Group 1) and OCT (Group 2 and 3) reinforced PMMA acrylic dentures were fabricated on the edentulous ridge. Ten PMMA dentures without reinforcement (Group 4) were included as controls. All specimens were placed in a chewing simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Fiberglass is an inorganic material that varies according to its composition (A, C, D, E, R and S glass), presenting adequate aesthetics, high tensile strength, low thermal conductivity, high corrosion resistance and adequate surface chemistry, which allows its adhesion to the resin-based materials. However, it presents some limitations such as brittleness and low wear resistance [ 13 ]. Polyethylene fibers are constituted of aligned polymer chains with low density modulus, which enables higher impact strength.…”
Section: Introductionmentioning
confidence: 99%
“…Fiberglass is an inorganic material that varies according to its composition (A, C, D, E, R and S glass), presenting adequate aesthetics, high tensile strength, low thermal conductivity, high corrosion resistance and adequate surface chemistry, which allows its adhesion to the resin-based materials. However, it presents some limitations such as brittleness and low wear resistance [ 13 ]. Polyethylene fibers are constituted of aligned polymer chains with low density modulus, which enables higher impact strength.…”
Section: Introductionmentioning
confidence: 99%
“…Primarily, the rough surface and porosity of PMMA materials facilitate the colonization of microorganisms, such as Candida albicans, Streptococcus sanguineus, and Streptococcus mutans, thereby propelling the incidence of various oral diseases ( An et al., 2022 ; Moreno-Maldonado et al., 2012 ; Quassem and Mahross, 2018 ; Sahm et al., 2022 ; Pourhajibagher et al., 2023 ; Schubert et al., 2019 ; Al-Dwairi et al., 2019 ; Patil et al., 2020 ; Dantas et al., 2016 ). Moreover, PMMA material exhibits a challenge regarding mechanical strength, proving susceptible to breakage under masticatory pressures ( Zafar, 2020 ; Ali Sabri et al., 2021 ; Alkordy and Alsaadi, 2014 ; Mohd Farid et al., 2022 ; Khan et al., 2022 ; Oleiwi et al., 2019 ; Zafar, 2018 ; Rana et al., 2021 ). Considering the myriad and multifaceted bacteria present in the human oral cavity, alongside the insufficient physical and mechanical strength of PMMA materials, an imperative arises to enhance the antibacterial properties of PMMA materials without compromising their physical and mechanical attribute.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used denture base material for production of removable dentures is heat cured polymethyl methacrylate (PMMA) acrylic resin [1]. Due to its favorable properties such as biocompatibility, superior aesthetic view, low water sorption, ease of modification, capability of being repaired, and ease and simplicity in processing achieved a great success in clinical dentistry [2].…”
Section: Introductionmentioning
confidence: 99%
“…Orthopedic casting tape (OCT) which is basically formed by a mesh made from glass fibers and a self curing resin surrounding the mesh, has been used for fracture management of long bones and provides excellent outcomes of immobilization and rigid support in the field of orthopedics. However, their potential in denture reinforcement still needs to be investigated [1]. From the available indexed literature, it was observed that inadequate data is available about the mechanical properties of complete dentures reinforced using glassfiber mesh.…”
Section: Introductionmentioning
confidence: 99%